Resonant Multiple Light Scattering for Photon Harvest Enhancement in Dye-Sensitized Solar Cells. Issue 1737 (8th June 2015) - Kim, Jihun; Lee, Horim; Seo, Yongsok
ABSTRACT: We have set a new bench mark for DSSC performances by fabricating a very efficient device with a high photocurrent density and good stability. This bench mark was accomplished by harmonizing the absorption spectrum of the dye with the average size of the aggregates in the TiO2 electrode. The resultant resonant multiple scattering enhanced the light harvesting efficiency and charge collection yield. The high and robust photovoltaic performance (with an initial efficiency of 9.18% and an efficiency of 7.44% after 800 h of irradiation with a light intensity of 100 mW cm -2 ) of the JH-1 DSSC prepared without an antireflecting layer demonstrated the promise of this novel sensitizer for large scale applications.